Occupational risk of COVID-19 related hospital admission in Denmark 2020-2021: a follow-up study - Jens Peter Ellekilde Bonde; Lea Sell; Esben Meulengracht Flachs; David Coggon; Maria Albin; Karen Marieke Oude Hengel; Henrik Kolstad; Ingrid Sivesind Mehlum; Vivi Schlünssen; Svetlana Solovieva; Kjell Torén; Kristina Jakobsson; et al. (Nordic Association of Occupational Safety and Health (NOROSH), 2023)
OBJECTIVE: Mounting evidence indicates increased risk of COVID-19 among healthcare personnel, but the evidence on risks in other occupations is limited. In this study, we quantify the occupational risk of COVID-19-related hospital admission in Denmark during 2020-2021. METHODS: The source population included 2.4 million employees age 20-69 years. All information was retrieved from public registers. The risk of COVID-19 related hospital admission was examined in 155 occupations with at least 2000 employees (at-risk, N=1 620 231) referenced to a group of mainly office workers defined by a COVID-19 job exposure matrix (N=369 341). Incidence rate ratios (IRR) were computed by Poisson regression. RESULTS: During 186 million person-weeks of follow-up, we observed 2944 COVID-19 related hospital admissions in at-risk occupations and 559 in referents. Adjusted risk of such admission was elevated in several occupations within healthcare (including health care assistants, nurses, medical practitioners and laboratory technicians but not physiotherapists or midwives), social care (daycare assistants for children aged 4-7, and nursing aides in institutions and private homes, but not family daycare workers) and transportation (bus drivers, but not lorry drivers). Most IRR in these at-risk occupations were in the range of 1.5-3. Employees in education, retail sales and various service occupations seemed not to be at risk. CONCLUSION: Employees in several occupations within and outside healthcare are at substantially increased risk of COVID-19. There is a need to revisit safety measures and precautions to mitigate viral transmission in the workplace during the current and forthcoming pandemics.